The role of collective analysis and self-reflection in adolescent leadership development (Eurasian Journal of Learning and Academic Teaching, 2024)
This article provides information on some approaches to social analysis and the role of self-determination in modern society, which take a fresh look at complex problems, reveal important human qualities such as mobility, initiative, competitiveness, and leadership in the universe.